An Analysis of Grammatical Errors in Thesis Abstracts and Strategies for Improvement - Noviyanti, Sari Dewi (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study examines grammatical errors in English-language thesis abstracts by students at an Islamic Higher Education institution in Central Java and proposes strategies for improvement. Employing a mixed-methods design, the research analyzed 50 randomly selected abstracts from seven faculties, published between 2021 and 2023, using James’ (1998) error analysis framework (grammatical, substantive, lexical, syntactic, and semantic errors) and APA 7th edition guidelines. Data collection involved quantitative error categorization and qualitative insights from surveys and interviews with students and stakeholders. Findings reveal 2,616 errors, with grammatical (24%), substantive (21%), and lexical (23%) errors being most prevalent, alongside incomplete structures in 80% of abstracts. Key causes include interlingual (L1 interference) and intralingual (English complexity) factors, compounded by inadequate guidelines and oversight. These errors undermine clarity and credibility in academic writing. The study recommends providing clear abstract writing guidelines, specialized courses, workshops, and robust evaluation systems, including grammar-checking tools and faculty-led reviews, to enhance writing quality. Implications suggest that improved training can elevate students’ scholarly communication skills and institutional academic standards. Limitations include the small sample size (50 abstracts), which may not fully represent the student population, and a sole focus on English writing. Future research should expand sampling, explore error causes qualitatively, and assess intervention effectiveness longitudinally.